2015
DOI: 10.1186/s12985-015-0297-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time reverse transcription loop-mediated isothermal amplification method for the rapid detection of porcine epidemic diarrhea virus

Abstract: BackgroundPorcine epidemic diarrhea (PED) is an acute and highly contagious enteric disease characterized by severe enteritis, vomiting and watery diarrhea in swine. Recently, the outbreak of the epidemic disease has been a serious problem in swine industry. The objective of this study is to develop a rapid, sensitive, and real-time reverse transcription loop-mediated isothermal amplification (RT-LAMP) method for the detection of porcine epidemic diarrhea virus (PEDV) in less equipped laboratories.ResultsThe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…SADS-CoV N gene was specifically amplified with a detection limit of 1.0 × 10 1 copies/μL and had good reproducibility. The sensitivity of the LAMP assay is similar to real-time RT-PCR (Yu et al, 2015). In this study, the RT-LAMP correctly identified 20 out of 24 samples as positive, showing similar diagnostic sensitivity comparable to the real time RT-PCR.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…SADS-CoV N gene was specifically amplified with a detection limit of 1.0 × 10 1 copies/μL and had good reproducibility. The sensitivity of the LAMP assay is similar to real-time RT-PCR (Yu et al, 2015). In this study, the RT-LAMP correctly identified 20 out of 24 samples as positive, showing similar diagnostic sensitivity comparable to the real time RT-PCR.…”
Section: Discussionsupporting
confidence: 61%
“…LAMP technology is currently used for the nucleic acid detection of a number of animal pathogens (Niessen et al, 2013;Sahoo et al, 2016). The assay offers multiple advantages compared to conventional PCR including a shorter turnaround time (30-60 min) and a sensitivity 1-2 orders of magnitude higher (Huang et al, 2016;Yu et al, 2015). In the present study, the real-time RT-LAMP method was used to detect SADS-CoV and did not cross-react with other porcine pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The PEDV M protein is a highly conserved trans-membrane protein that is the most abundant envelope component [13,14]. Two reports have shown that the developed RT-LAMP method for the PEDV M gene has a higher sensitivity than the RT-LAMP method developed for the N gene [15,16]. The use of LAMP for detecting PEDV has been reported [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Loop-mediated isothermal amplification (LAMP) is an amplification gene technique developed some years ago (Notomi et al, 2000) which allows to amplify nucleic acids in an hour and under isothermal conditions, and to evaluate the results by observation of the turbidity of the reaction or using different dyes. Reverse transcriptase LAMP (RT-LAMP) has been used to amplify the genome of several coronaviruses of both humans and animals (Amer et al, 2013;Bhadra et al, 2015;Cardoso et al, 2010;Hanaki et al, 2013;Nemoto et al, 2015;Pyrc et al, 2011;Thai et al, 2004;Yu et al, 2015). To our knowledge, RT-LAMP has never been used for the identification of FCoVs.…”
Section: Introductionmentioning
confidence: 99%